2015
DOI: 10.1039/c4an02028f
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared excited ultraviolet emitting upconverting phosphors as an internal light source in dry chemistry test strips for glucose sensing

Abstract: Upconverting phosphors are inorganic crystals with interesting optical properties, including the ability to convert infrared radiation to emission at shorter wavelengths. In this paper we present the utilization of nanosized β-NaYF4:Yb(3+),Tm(3+), synthesized in the presence of K(+), emitting at 365 nm under 980 nm excitation as an internal light source in glucose sensing dry chemistry test strips. The feasibility of the nanoparticles as an internal UV light source was compared to the use of an external broadb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This is caused by the higher standard deviation of the UCP signals that counteract the benefit of the steeper slope. A similar effect was reported in our previous study [28] in which the UCP signal was significantly stabilized by using another emission peak as an internal control signal. As the attenuation of the excitation affects all of the emissions of the UCP, this approach is not possible and the composition of the test strips should be optimized to better accommodate the upconverting particles.…”
Section: Determination Of Glucosesupporting
confidence: 87%
“…This is caused by the higher standard deviation of the UCP signals that counteract the benefit of the steeper slope. A similar effect was reported in our previous study [28] in which the UCP signal was significantly stabilized by using another emission peak as an internal control signal. As the attenuation of the excitation affects all of the emissions of the UCP, this approach is not possible and the composition of the test strips should be optimized to better accommodate the upconverting particles.…”
Section: Determination Of Glucosesupporting
confidence: 87%
“…It is important to mention that applications exist, where B is not the major figure of merit. When the sensitivity and limit of detection are directly linked to the distance between emissive donor ions (here Ho 3+ ) and acceptor molecules (e.g., antibody‐bound fluorophores or stimuli‐responsive dyes) as required for Förster resonant energy transfer (FRET) phenomenon, particle structures are desired where the donors are located close to the UCNP surface . For example, for FRET biosensors, Yb@YbHo@… seems to be preferable than other architectures.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly it is revealed that (i) the emission shows all the three red-green-blue (RGB) main colors including the most-difficult-to-obtain blue color, (ii) these are achieved with both three- and two-photon processes, and (iii) the emission intensity is highly angle-dependent. The latter observation is extremely intriguing for application in ultrasensitive fluorescence assays and surface sensors for point-of-care diagnostics. …”
Section: Introductionmentioning
confidence: 99%